Automatic safety evaluation and visualization of subway station excavation based on BIM-FEM/FDM integrated technology - Xie, Ping; Zhang, Rongjun; Zheng, Junjie; Li, Ziqian (Journal of Civil Engineering and Management, 2022)
With the progressive promotion of BIM technology in collaborative design and engineering data management, there are large amounts of project information available for intelligent construction, engineering computation and design optimization. In the construction of subway station, BIM technology is still not mature and the engineering design is generally separate from the engineering safety evaluation. Thus, this paper proposed a technology that integrates BIM and numerical simulation (BIM-FEM/FDM integrated technology) to solve the problem of separation between engineering design and computation. A three-dimensional parametric modeling of subway station excavation was first carried out using the Revit® modeling software. Afterward, a FEM/FDM-process oriented data conversion interface was developed to extract and process the critical information from the parametric BIM model for numerical simulation. Then, under the impetus of an auto-simulation interface, the safety evaluation of subway station excavation was realized automatically and visualized graphically. The research of the BIM-FEM/FDM integrated technology presented in this paper has established a supporting platform to achieve the integration of BIM-based design and safety evaluation for subway station excavation.